2018
DOI: 10.3390/met8020147
|View full text |Cite
|
Sign up to set email alerts
|

Processing Effects on the Formability of Magnesium Alloy Sheets

Abstract: Abstract:As a generalized semi-finished product, the use of magnesium sheets requires addressing two major aspects of their processing: their microstructure and texture control, which are both essential for the forming behavior of such sheets during their forming to parts. Further, the processing of such sheets is complex, and therefore expensive, and requires simplification. In this work, magnesium alloys AZ31, ZE10, and ME21 are investigated in the form of conventionally rolled sheets, as well as in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The variation of the intensities is small. This texture results are typical for AZ31 and compare well to those of rolled or extruded sheets of this alloy (Styczynski et al, 2004;Yi et al, 2006;Victoria-Hernandez et al, 2014;Bohlen et al, 2018a).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The variation of the intensities is small. This texture results are typical for AZ31 and compare well to those of rolled or extruded sheets of this alloy (Styczynski et al, 2004;Yi et al, 2006;Victoria-Hernandez et al, 2014;Bohlen et al, 2018a).…”
Section: Resultssupporting
confidence: 74%
“…Accommodation of such strain may require the same orientation considerations as above, but they are especially needed homogeneously in all in-plane directions. Although sample dimensions in this study did not allow revealing the mechanical behavior along the transverse direction, it has been shown in earlier work on extruded sheets that a strong anisotropy of the mechanical behavior is often correlated to limited stretch formability (Bohlen et al, 2018a). Forming limit curves revealed low formability in stretch forming conditions on the right side of the forming limit diagram but high formability on the left side, which in the context of this study compares to a strain path of the uni-axial tension test.…”
Section: Mechanical Properties and Formabilitymentioning
confidence: 90%
See 2 more Smart Citations
“…In case of a weakened basal-type texture or non-basal texture components, it is expected that <a> dislocations with a relatively low CRSS contribute to accommodating the deformation along the ND. It was reported that texture weakening can be achieved by alloying Mg with yttrium (Y) and rare earth (RE) elements 2 of 9 such as cerium (Ce) or neodymium (Nd) [1][2][3][4][5]. Indeed, increased ductility, formability and strength have been observed in the sheet that has a weaker texture [6].…”
Section: Introductionmentioning
confidence: 99%